THE ROLE OF INFORMED CONSENT IN PAEDIATRIC SURGERY IN INDONESIA - Trismayanti, Ni Made Rika; Nurmawati, Bernadete; Darmawansyah, Adi (International Journal of Cultural and Social Science, 2026)
Informed Consent (IC) plays an important role in determining the fate of pediatric patients, especially children who require medical treatment in the form of surgery. Children are considered legally incapable of giving legal consent to medical procedures because they have not reached adulthood, so the responsibility is given to a parent or legal guardian. Without the consent of the parents, medical procedures cannot be performed on pediatric patients. The purpose of this article is to find out how the regulation and role of IC in the practice of Paediatric Surgery in Indonesia is based on applicable regulations. The research method used is a normative juridical method. The findings obtained are that IC in the practice of Paediatric Surgery in Indonesia is regulated in Law No. 29 of 2004 concerning Medical Practice and Permenkes No. 290/Menkes/Per/III/2008 concerning the Approval of Medical Measures. In pediatric surgical procedures, IC is given by parents as the closest family based on the consideration of the best efforts for the benefit of the child, as well as protection for medical personnel in carrying out their duties. However, existing regulations do not yet regulate the protection of children's rights against parents who reject IC. In the future, it is hoped that IC pediatric surgical practice will be carried out with full understanding and wise decisions from all parties involved, in accordance with legal principles and medical ethics.